The Use of Ladder Snake Games to Improve Learning Outcomes in Computer Networking - Patmanthara, Syaad; Yuliana, Oki Dwi; Dwiyanto, Felix Andika; Wibawa, Aji Prasetya (International Journal of Emerging Technologies in Learning (iJET), 2019)
Educational games enable students to learn and play. The use of educational games as learning media can also encourage users to discover and build their own knowledge of learning. The purpose of this study is to show the impact of using educational games on student learning outcomes. Educational games can be used as an alternative choice as a learning media. The research instruments used were post test and pre test. Data analysis was done by comparing the results of the post test and pre test. This analysis was conducted to see whether there were changes in student learning outcomes. The results shows that students’ learning outcome are increase by implementing educational games.